👤

1. 7a3 - a2 + 11 + (a3 - 2a2 - 5)
2. Subtract 5y2 - 3y - 4 from 2y2 - 3y + 7.


Sagot :

[tex]\large\underline{\mathcal{SOLUTION}}:[/tex]

7a3 - a2 + 11 + (a3 - 2a2 - 5)

  • = 7a³ - a² + 11 + a³ - 2a² - 5
  • = 7a³ - a³ - a² - 2a² + 11 - 5
  • = 7a³ - a³ - a² - 2a² + 6
  • = 8a³ - a² - 2a² + 6
  • = 8a³ - 3a² + 6

5y2 - 3y - 4 - (2y2 - 3y + 7)

  • = 5y² - 3y - 4 - 2y² - 3y + 7
  • = 5y² - 2y² - 3y + 3y - 4 - 7
  • = 5y² - 2y² - 4 - 7
  • = 5y² - 2y² - 11
  • = 3y - 11

[tex]\large\underline{\mathcal{ANSWER}}:[/tex]

  1. 8a³ - 3a² + 6
  2. 3y - 11

#CarryOnLearning

[tex]\huge\red{\boxed{\tt{{ANSWER:}}}}[/tex]

[tex]\huge\orange{\overline{\quad\quad\quad\quad\quad\quad\quad\quad }}[/tex]

1.

 [tex]\implies \large\purple{\boxed{\tt{{ 7a_3 - a_2 +11+(a3-2a2-5)}}}}\\\implies \large\purple{\boxed{\tt{{ 8a_{3}-a_{2}+11-2a_2-5}}}}\\\implies \large\purple{\boxed{\tt{{ 8a_3-3a_2+11-5}}}}\\\implies \huge\purple{\boxed{\tt{{ 8a_3-3a_2+6}}}}[/tex]

2.

[tex]\implies \large\purple{\boxed{\tt{{ 5y^2-3y-4-2y^2-3y+7}}}}\\\implies \large\purple{\boxed{\tt{{ 5y^2-2y^2-3y+3y-4-7}}}}\\\implies \large\purple{\boxed{\tt{{ 5y^2-2y^2-4-7}}}}\\\implies \large\purple{\boxed{\tt{{ 5y^2-2y^2-11}}}}\\\implies \huge\purple{\boxed{\tt{{ 3y-11}}}}[/tex]

[tex]\huge\orange{\overline{\quad\quad\quad\quad\quad\quad\quad\quad }}[/tex]

[tex]\large\color{pink}{\boxed{\boxed{\colorbox{pink}{\tt{\color{red}{G\color{blue}{O\color{green}{O\color{lime}{D\color{skyblue}{D\color{cyan}{A\color{blue}{Y\color{purple}{<3}}}}}}}}}}}}}[/tex]

#MagnificentSquad

#CarryOnLearning

#BrainlyFast